2016
DOI: 10.1364/oe.24.016586
|View full text |Cite
|
Sign up to set email alerts
|

Optical constants of CH_3NH_3PbBr_3 perovskite thin films measured by spectroscopic ellipsometry

Abstract: The lack of optical constants information for hybrid perovskite of CH3NH3PbBr3 in thin films form can delay the progress of efficient LED or laser demonstration. Here, we report on the optical constants (complex refractive index and dielectric function) of CH3NH3PbBr3 perovskite thin films using spectroscopic ellipsometry. Due to the existence of voids, the refractive index of the thin films is around 8% less than the single crystals counterpart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 36 publications
6
79
0
Order By: Relevance
“…For example, Quarti et al reported experimental E g valueso f1.65, 1.61, and 1.69 eV for the orthorhombic (4 K), tetragonal (160 K), and pseudocubic (330 K) phases of CH 3 NH 3 PbI 3 . [127] These data show am arginal variation in E g valuesb etween the three phases (all within 0.17 eV), which is unsurprising, according to Leguy et al [128,129] In agreement with the view of Leguy et al, [128] we further noted that there has been aw ide variation in the experimentally determined band gaps reported for CH 3 NH 3 PbBr 3 .T his variation originated from different research groupsw ith different experimental settings to give E g values of 2.33, [86] 2.309, [131] 2.24, [128] and 2.12 eV. [132] Similarly, E g values of 2.97, [128] 3.06, [86] and 3.11eV [91,130] werer eportedf or CH 3 NH 3 PbCl 3 ,a nd so on.…”
Section: Computational Detailssupporting
confidence: 86%
See 1 more Smart Citation
“…For example, Quarti et al reported experimental E g valueso f1.65, 1.61, and 1.69 eV for the orthorhombic (4 K), tetragonal (160 K), and pseudocubic (330 K) phases of CH 3 NH 3 PbI 3 . [127] These data show am arginal variation in E g valuesb etween the three phases (all within 0.17 eV), which is unsurprising, according to Leguy et al [128,129] In agreement with the view of Leguy et al, [128] we further noted that there has been aw ide variation in the experimentally determined band gaps reported for CH 3 NH 3 PbBr 3 .T his variation originated from different research groupsw ith different experimental settings to give E g values of 2.33, [86] 2.309, [131] 2.24, [128] and 2.12 eV. [132] Similarly, E g values of 2.97, [128] 3.06, [86] and 3.11eV [91,130] werer eportedf or CH 3 NH 3 PbCl 3 ,a nd so on.…”
Section: Computational Detailssupporting
confidence: 86%
“…In agreement with the view of Leguy et al., we further noted that there has been a wide variation in the experimentally determined band gaps reported for CH 3 NH 3 PbBr 3 . This variation originated from different research groups with different experimental settings to give E g values of 2.33, 2.309, 2.24, and 2.12 eV . Similarly, E g values of 2.97, 3.06, and 3.11 eV were reported for CH 3 NH 3 PbCl 3 , and so on.…”
Section: Resultsmentioning
confidence: 87%
“…Temperature-dependent measurements can help to develop a more complete picture of these optical properties, which needs to include identification of exciton binding energies, free carriers, as well as direct and possible indirect transitions. Direct measurements of optical absorption spectra of single crystals in transmission are hindered by the short absorption length of visible light in OIPS [52], which forms a basis of their successful application in optoelectronics. Measurements in reflectance are surface-sensitive, and easily affected by hydration of the surface [35,45].…”
Section: Introductionmentioning
confidence: 99%
“…obtain the E-k dispersion relation of exciton-polariton for NWs on SiO2/Ag substrates, the background dielectric constant b  and damping constant  need to be determined (SI Note 1). The background dielectric constant is calculated from the spectroscopic ellipsometer [51][52][53]. With the dielectric function ε(E) = ε1(E) + iε2(E) and the refractive index N(E) = n(E) + ik(E) ranging over a wide photon-energy, the n and k could be obtained from the spectroscopic ellipsometer and finally the background dielectric constant b  can be calculated as ε1 = n 2 -k 2 and b  is dielectric constant located at    .…”
mentioning
confidence: 99%